LOCATION SELECTION STUDY FOR THE FISH LANDING BASE IN KESUMA VILLAGE PANGKALAN KURAS SUB-DISTRICT PELALAWAN DITRICT RIAU PROVINCE - Herlina, Cici; Isnaniah, Isnaniah; Syaifuddin, Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABCTRACTThis study aims to determine the location of fish landing sites that are better and more precise than platforms managed by toke or fish collectors which are usually used as landing sites for the catches of fishing communities around Kesuma Village. This research activity was carried out in December 2019. Data collection was carried out in Kesuma Village, PangkalanKuras District, Pelalawan Regency, Riau Province. The method used is the servei method with the number of respondents as many as 7 ship owners with census sampling.The results showed that the landing site A is the best location to be recommended in planning the construction of fish landing sites. Pelantar A with the highest total final score of 236.21 points, which means that the specified criteria parameters such as technical condition, fishery potential, socio-economic community and infrastructure have been met. Judging from the data obtained, the type of port that is suitable to be built at the port location A is a type D fishing port, namely a fish landing base (PPI).Keywords:Selection location, the fishing port, Kuala Terusan Villlage